2021
DOI: 10.3390/bioengineering8090119
|View full text |Cite
|
Sign up to set email alerts
|

Pichia pastoris (Komagataella phaffii) as a Cost-Effective Tool for Vaccine Production for Low- and Middle-Income Countries (LMICs)

Abstract: Vaccination is of paramount importance to global health. With the advent of the more recent pandemics, the urgency to expand the range has become even more evident. However, the potential limited availability and affordability of vaccines to resource low- and middle-income countries has created a need for solutions that will ensure cost-effective vaccine production methods for these countries. Pichia pastoris (P. pastoris) (also known as Komagataella phaffii) is one of the most promising candidates for express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 126 publications
0
9
0
Order By: Relevance
“…Development of facilities needed to produce mRNA therapeutics in massive quantities has been and is currently underway, with infrastructure capable of producing tens of millions of these products for vaccination and related applications [96]. The market value of vaccine production is also predicted to increase from 28 billion dollars reported in 2017 to over 80 billion dollars by 2027, with a CAGR of 8.7% [97]. With this increase in vaccine production worldwide, an updated view of vaccine manufacturing methods is required.…”
Section: Vaccinesmentioning
confidence: 99%
“…Development of facilities needed to produce mRNA therapeutics in massive quantities has been and is currently underway, with infrastructure capable of producing tens of millions of these products for vaccination and related applications [96]. The market value of vaccine production is also predicted to increase from 28 billion dollars reported in 2017 to over 80 billion dollars by 2027, with a CAGR of 8.7% [97]. With this increase in vaccine production worldwide, an updated view of vaccine manufacturing methods is required.…”
Section: Vaccinesmentioning
confidence: 99%
“…1,2 P. pastoris has already been proven repeatedly to allow high level recombinant protein production. 3,4,5,6 It is known from literature that recombinant protein production causes a metabolic burden on cellular metabolism. The phenotype of cells producing recombinant proteins can be a decreased growth rate, decreased biomass formation, and overall decreased cell fitness.…”
Section: Introductionmentioning
confidence: 99%
“…as the major players 1,2 . P. pastoris has already been proven repeatedly to allow high level recombinant protein production 3,4,5,6 …”
Section: Introductionmentioning
confidence: 99%
“…Yeast is a workhorse for the production of vaccines due to expression of different forms of antigens that can be scalable with reasonable cost. Among several yeast species, Pichia pastoris is considered one of the most promising options for heterologous protein production in vaccine development [ 8 ]. P. pastoris synthesizes high cell densities under a controlled environment and the cell lines are genetically stable in terms of the post translational modifications of protein in the endoplasmic reticulum (ER) and resistance to contamination.…”
mentioning
confidence: 99%
“…It has already been reported that more than 500 heterologous proteins have been successfully expressed using this host, with several of them being approved for human and commercial use. Human insulin (SuperMan5) and recombinant hepatitis C (HCV) are good examples of recombinant protein expressed in P. pastoris [ 8 ].…”
mentioning
confidence: 99%